2018
DOI: 10.1016/j.jphs.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Factor Xa inhibition by rivaroxaban attenuates cardiac remodeling due to intermittent hypoxia

Abstract: Patients with obstructive sleep apnea (OSA) have a high prevalence of atrial fibrillation (AF). Rivaroxaban, a coagulation factor Xa inhibitor, has recently been reported to show pleiotropic effects. This study investigated the influence of rivaroxaban on cardiac remodeling caused by intermittent hypoxia (IH). Male C57BL/6J mice were exposed to IH (repeated cycles of 5% oxygen for 1.5 min followed by 21% oxygen for 5 min) for 28 days with/without rivaroxaban (12 mg/kg/day) or FSLLRY, a protease-activated recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…While rivaroxaban at the highest concentration (5.6 mM) did not affect the mitochondrial ROS generation. These results are in agreement with previous studies that showed rivaroxaban has been able to reduce ROS generation [19,20].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…While rivaroxaban at the highest concentration (5.6 mM) did not affect the mitochondrial ROS generation. These results are in agreement with previous studies that showed rivaroxaban has been able to reduce ROS generation [19,20].…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, rivaroxaban may cause complications due to accumulation and elimination through the kidney [16][17][18]. Previous studies have shown that rivaroxaban has been able to reduce the level of ROS [19,20]. Furthermore, the rivaroxaban has reduced the inflammatory signal caused by FXa [21].…”
Section: Introductionmentioning
confidence: 99%
“…How coagulation promotes AAA and the role of inflammation is not clear. A recent study found that the FXa inhibitor rivaroxaban prevents NFkB activation in a murine model of inflammation-driven cardiac remodeling (40). Here we found that genetic deletion of Alox15 significantly abrogated the ability of Ang II to elevate both IL6 and CCL2 gene expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In carotid bodies, IH-induced ROS generation is associated with HIF-1 activity and results in a sensory long-term facilitation of carotid bodies [39,40,41]. Several in vivo and in vitro studies have also observed that IH induces the activation of NF-κB in cardiovascular tissues and endothelial cells [42,43,44,45]. Our previous research, using reporter gene assays, also confirmed that IH induces the activation of NF-κB in cultured rat aortic smooth muscle cells (RASMCs) [34].…”
Section: Reactive Oxygen Species (Ros) and Transcriptional Factorsmentioning
confidence: 99%